Evaluation of the cognitive level of essay questions of an undergraduate medical program in Sri Lanka, using bloom’s taxonomy - Deepthika Himali Edussuriya; Roshitha Nilmini Waduge; M. D. Lamawansa; Achini Nuwangika Samaranayake (Sri Lanka Journal of Medicine, 2018)
Background:  Medical curricula should encourage the development of advanced cognitive skills. Examination questions are an indicator of the cognitive level expected of students. However, it is believed that many factors, such as difficulty in maintaining objectivity in marking, large numbers of scripts and poor language ability of students lead to compiling of essay questions requiring lower cognitive levels.